Multidisciplinary Education and the Growth of Social Competence in Children - Hariani, Mila; Safira, Mirza Elmy; Wahyuni, Sri (Journal of Social Science Studies, 2021)
As global dynamics increasingly demand collaborative, emotionally intelligent citizens, education must evolve to address the social and emotional growth of children. This study explores how multidisciplinary approaches enhance children's social and emotional skill development, particularly within peer and familial contexts. Drawing on literature from psychology, education, and sociology, the analysis reveals that integrated curricula support competencies such as empathy, self-regulation, cooperation, and reflective communication. Through interdisciplinary methods—such as narrative-based learning, collaborative inquiry, civic engagement, and arts integration—students experience diverse modalities for emotional expression and social understanding. Furthermore, the incorporation of physical education and digital literacy broadens the platforms through which children build relational fluency. The findings underscore that when schools align pedagogical design with interdisciplinary frameworks, they offer children tools that not only enrich academic performance but cultivate meaningful, compassionate relationships. The study recommends embedding social-emotional goals across all subjects and preparing educators through comprehensive professional development. Ultimately, fostering relational competencies through multidisciplinary learning equips learners to engage with empathy and agency across social environments.